Jancuk as an Expressive Speech Act: a Sociolinguistic Study in Non-Javanese Speakers - Nurfalah, Fauzan; Nandang, Ade; Musthafa, Izzuddin (Sutasoma : Jurnal Sastra Jawa, 2025)
The word “jancuk” is a form of speech often used in daily conversation, especially in the Arekan dialect spoken in some regions of East Java, such as Surabaya, Malang, and Lumajang. However, in the development of language, this speech is also adapted by non-Javanese speakers with various communication functions, such as in West Java, to be the origin of the Sundanese people, as well as outside the island of Java. This study aims to analyze “jancuk” as an expressive speech act, particularly in the sociolinguistic context of non-Javanese speaking communities. Using a sociopragmatic qualitative approach, this study examines the use of “jancuk” speech in social interactions and how it functions as an expression of emotions, solidarity, and group identity by identifying the instances of “jancuk” use. The results of the study showed that the expression “jancuk” experienced a shift in meaning when used by non-Javanese speakers, with a more flexible application in various communication situations.